2021
DOI: 10.1007/s00345-021-03825-z
|View full text |Cite
|
Sign up to set email alerts
|

Experimental ex-vivo performance study comparing a novel, pulsed thulium solid-state laser, chopped thulium fibre laser, low and high-power holmium:YAG laser for endoscopic enucleation of the prostate

Abstract: Purpose The aim of this study was to compare the enucleation performances of four different types of laser devices in an ex-vivo experiment: a novel, pulsed Tm:YAG solid-state laser evaluation model (p-Tm:YAG), chopped thulium fibre laser (TFL), low-power Ho:YAG laser (LP-Ho:YAG), and a high-power Ho:YAG laser (HP-Ho:YAG). Methods Our primary aim was to endoscopically separate the fascial layers of a porcine belly using laser fibres within a time period of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…If our assumption is correct, carbonization may also be lower when using TFL. In comparing TFL and pulsed Tm : YAG (27), no significant differences were found. That can be explained by the change of laser pulse generation.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…If our assumption is correct, carbonization may also be lower when using TFL. In comparing TFL and pulsed Tm : YAG (27), no significant differences were found. That can be explained by the change of laser pulse generation.…”
Section: Discussionmentioning
confidence: 77%
“…Yilmaz et al (27) in their study tried to simulate the prostate enucleation process using a model of porcine belly. The researchers compared the speed of anterior abdominal wall fascial layers with separation, coagulation performance of lasers and the ease with which the surgeon could operate.…”
Section: Thulium Fiber Laser For Soft Tissuesmentioning
confidence: 99%
“…Discussions about possible safety differences between TFL and holmium laser arose from the same reasons as mentioned above regarding functional outcomes [ 11 ]. The first ex vivo trials showed significant differences between the laser sources with improved hemostatic effect [ 11 , 14 , 16 ]. On the contrary, one ex vivo trial showed comparable coagulation between the two laser sources and another ex vivo trial even postulated a significant better coagulation with the holmium laser than with TFL [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tissue rupturing due to fast vaporization of the water between laser fiber and tissue as it is typical for the holmium laser may achieve better tissue separation than a sharp incision which is typical for the TFL [ 11 ]. In two ex vivo trials the tissue separation depth was greater with the holmium laser than TFL and objectively preferred by the surgeons [ 16 , 25 ]. In three in vivo studies available to date, ThuFLEP was equivalent to HoLEP in terms of enucleation time and efficiency [ 10 , 12 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation